Bilateral Uterine Artery Embolization as a Rescue Method in a Rare Case of Cervical Ectopic Pregnancy - Gupta, Pooja; Rekha, B. S. V. B.; Yadav, Deep; Rasheed, Mohd; Jain, Charu (Journal of Clinical Interventional Radiology ISVIR, 2024)
Cervical pregnancy, being the second rarest form of ectopic pregnancy after abdominal pregnancy, is a difficult clinical entity to diagnose and manage in a young primigravida with no identifiable risk factors or associated symptoms. Further, early intervention is of utmost importance owing to the deleterious complications and high mortality associated with it if not addressed to. It is also difficult to choose a particular management approach for this out of the available options. We report a case of 23-year-old primigravida with 8 weeks of gestation, asymptomatic and with no underlying risk factors, diagnosed with cervical pregnancy during a routine antenatal scan. She was successfully managed with bilateral uterine artery embolization in conjunction with systemic methotrexate followed by suction and evacuation.
Keywords: cervical; ectopic; embolization